Tracing the Development of Arabic Khat from the Land of Origin to Indonesian Archipelago - Azkia Muharom Albantani; Ahmad Adhia Adha; Aida Mushoffa; Helya Syafiroh (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2021)
Several studies showed that Arabic khat had been widely developed in countries with a Muslim majority population.